VideoDraw: A Video Interface for Collaborative Drawing - Tang, John (CHI '90 Proceedings of the SIGCHI Conference on Human Factors in Computing Systems, 1990)
This paper describes VideoDraw, a shared drawing tool, and the process by which it is being designed and developed. VideoDraw is a prototype, video-based, tool that provides a shared “virtual sketchbook” among two or more collaborators. It not only allows the collaborators to see each others’ drawings, but also conveys the accompanying hand gestures and the process of creating and using those drawings. Its design stems from studying how people collaborate using shared drawing spaces. Design implications raised by those studies were embodied in a prototype, which was in turn observed in use situations. Continued research studying the use of VideoDraw (in comparison with other collaborative media) will lead to a better understanding of collaborative drawing activity and inform